To model the situation, we can define the variables:
- Let \( t \) represent the number of weeks.
- Let \( M(t) \) be Maura's account balance after \( t \) weeks.
- Let \( B(t) \) be Brad's account balance after \( t \) weeks.
From the information given:
-
Maura's account balance after \( t \) weeks can be represented as: \[ M(t) = 2 + 82t \]
-
Brad's account balance after \( t \) weeks can be represented as: \[ B(t) = 83t \]
We need to find \( t \) when Maura's account balance equals Brad's account balance, which gives us the equation: \[ M(t) = B(t) \]
Substituting the expressions we found: \[ 2 + 82t = 83t \]
Now, we will solve for \( t \):
- Rearranging the equation gives: \[ 2 = 83t - 82t \] \[ 2 = t \]
Now that we found \( t = 2 \) weeks, we can find the account balance of both Maura and Brad after 2 weeks.
Calculating Maura's account balance: \[ M(2) = 2 + 82(2) = 2 + 164 = 166 \]
Calculating Brad's account balance: \[ B(2) = 83(2) = 166 \]
Thus, Maura and Brad will each have an account balance of $166 after 2 weeks. Therefore, we fill in the blanks:
Maura and Brad will each have an account balance of $ 166 after 2 weeks.